2001
DOI: 10.1107/s0108767301001325
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-resolved output analysis of X-ray multiple-wave interaction

Abstract: The polarization suppression of the interfering components in X-ray multiple-wave interaction is observed for the first time by using a polarization analyzer with an arbitrary inclination of the diffraction plane with respect to that of the investigated crystal. The condition for total suppression of the multiple-wave interaction outside the investigated crystals by a polarization analyzer is derived theoretically from the modified Born approximation. By means of the partial suppression of the strong interferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Since it was reported decades ago that information on the phases of the structure factors -or more precisely, on invariant triplet phases -could be accessed via X-ray multiple diffraction (XRMD) experiments (Lipscomb, 1949;Hart & Lang, 1961;Post, 1977;Chapman et al, 1981;Chang, 1984;Shen & Colella, 1987), many attempts have been made to use this phenomenon as a physical solution of the phase problem in X-ray crystallography or, at least, as a general tool for studying crystalline and nonperiodic materials (Tischler & Batterman, 1986;Rossmanith, 1992;Weckert & Hü mmer, 1997;Avanci et al, 1998;Stetsko et al, 2000Stetsko et al, , 2001Shen et al, 2000;Remé dios et al, 2005). In this latter context, XRMD can be seen as a method to provide specific pieces of information that could not be retrieved by any other method and thus make it possible to distinguish one atomic structure from another among several possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was reported decades ago that information on the phases of the structure factors -or more precisely, on invariant triplet phases -could be accessed via X-ray multiple diffraction (XRMD) experiments (Lipscomb, 1949;Hart & Lang, 1961;Post, 1977;Chapman et al, 1981;Chang, 1984;Shen & Colella, 1987), many attempts have been made to use this phenomenon as a physical solution of the phase problem in X-ray crystallography or, at least, as a general tool for studying crystalline and nonperiodic materials (Tischler & Batterman, 1986;Rossmanith, 1992;Weckert & Hü mmer, 1997;Avanci et al, 1998;Stetsko et al, 2000Stetsko et al, , 2001Shen et al, 2000;Remé dios et al, 2005). In this latter context, XRMD can be seen as a method to provide specific pieces of information that could not be retrieved by any other method and thus make it possible to distinguish one atomic structure from another among several possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, several authors have demonstrated that the linear polarization of synchrotron radiation can be used to change the relative strength of multiple diffracted waves [14,15] and/or improve phase sensitivity in some cases [16]. Polarization resolved n-BD has also been considered for enhancing phase sensitivity [17]. However, phase determination is more complex than just carrying out measurements at optimized phase sensitive conditions.…”
mentioning
confidence: 99%
“…The function f͑f͒ is the resonance term [11,13,17] describing the excitation of the secondary wave, D d , during the f rotation. In practice, simple functions can be used as the resonance term for fitting the azimuthal scans and extracting the triplet phases.…”
mentioning
confidence: 99%
See 1 more Smart Citation